Applicability of first‐trimester combined screening for fetal trisomy 21 in a resource‐limited setting in mainland China. (14th September 2016) - Li, B; Sahota, DS; Lao, TT; Xu, J; Hu, SQ; Zhang, L; Liu, QY; Sun, Q; Tang, D; Ma, RM
Abstract : Objective: To assess the feasibility and performance of the first‐trimester combined screening test for trisomy 21 in a resource‐limited setting in mainland China. Design: Prospective observational cohort study. Setting: First Affiliated Hospital of Kunming Medical University, China. Population: Ten thousand four hundred and forty‐two pregnant women requesting first‐trimester screening. Methods: The combined screening test was performed from May 2012 to December 2014. Women with a high‐risk result (≥1:600) were offered further confirmatory tests after counselling. The threshold for high risk was determined by Monte Carlo simulation to achieve a 5% false‐positive rate according to the local age distribution. Pregnancy outcome and screening results were recorded for all women and monthly audits were conducted. Main outcome measures: Sensitivity, screen positive rate, cost per case of Down syndrome detected. Results: Six hundred and ten women (5.8% of the total screened) had a high‐risk screening test, of whom 274 (44.9%) underwent a diagnostic test and 169 (27.7%) opted for a noninvasive prenatal screening test (NIPT); 160 (26.2%) declined further testing after counselling. The pregnancy outcome was available for 10 174 (97.4%) of the women. The observed incidence of Down syndrome was 0.13% (1/750). All 14 women with a trisomy 21 pregnancy had a high‐risk screening test result. The cost per Down syndrome detected was RMB596 686 compared with RMB1.79 million if all had been screened by NIPT. Conclusions: The combined screening test appears to be a more cost‐effective strategy in mainland China. Screening performance in China would be improved by adopting Chinese‐specific models, external quality control and assurance, and establishing risk thresholds appropriate for the age distribution of the population. Tweetable abstract: Combined first‐trimester Downs screening in China was improved by adopting Chinese‐specific models and external QC. Tweetable abstract: Combined first‐trimester Downs screening in China was improved by adopting Chinese‐specific models and external QC.